Promoting anti-corruption, transparency and accountability in the recruitment and promotion of health workers to safeguard health outcomes - Monica Twesiime Kirya (Taylor & Francis Group, 2020)
Background: Human Resources for Health are a core building block of a health system, playing a crucial role in improving health outcomes. While the existing literature has examined various forms of corruption that affect the health sector, few articles have examined the role and impact of corruption in the recruitment and promotion of health-workers. Objectives: This study reviews the role of corrupt practices such as nepotism, bribery and sextortion in health-worker recruitment and promotion and their implications for health systems. Methods: The study is based on an interdisciplinary non-systematic review of peer-reviewed journal articles in the public health/medicine and political science literature, complemented with the 'grey' literature such as technical reports and working papers. Results: Political and personal ties, rather than merit are often factors in the recruitment and promotion of health-workers in many countries. This results in the employment or promotion of poorly qualified or unsuitable workers, with negative implications for health outcomes. Conclusion: Corrupt practices in health-worker recruitment and promotion 'set the tone' for other forms of corruption such as absenteeism, embezzlement, theft and bid-rigging to flourish, as those recruited corruptly can collude for nefarious purposes. On the other hand, merit-based recruitment is important for curbing corruption. Corrupt recruitment practices have deleterious effects on health-worker motivation and retention, quality and competency, citizens' trust in health services and health outcomes. Whereas international law and policy such as the United Nations Convention Against Corruption and the WHO Handbook on Monitoring and Evaluation of Human Resources for Health state that recruitment of public officers and health workers respectively should be done in a transparent and accountable manner, more research is needed to inform policies on merit-based recruitment.